The Role of Local Governments In Improving The Quality of Human Development - Dany Syarifudin; Achmad Solihin (MediaTrend, 2022)
Local governments, through their own spending budgets, must intervene in improving the quality of human capital. Government spending on education and health is part of government spending that can encourage improvements in the quality of human capital. This study aims to determine the interaction relationship between government spending and human development. This research was conducted in 491 districts / cities in the 2010-2019 time period. The use of the Fully Modified OLS (FMOLS) analysis method with panel data. The results of this study indicate that the interaction of government spending on education and health has a long-term impact on improving the quality of human development. Government spending on education and health is known to have a positive effect on improving human capital. The importance of public investment for improving the quality of human capital through education and health so as to increase the standard of living and welfare of the community.